The Difference in Surgical Site Infection Rates Between Open and Minimally Invasive Spine Surgery for Degenerative Lumbar Pathology: A Retrospective Single Center Experience of 1442 Cases. Issue 6 (9th August 2018) - Mueller, Kyle; Zhao, David; Johnson, Osiris; Sandhu, Faheem A; Voyadzis, Jean-Marc
Abstract: BACKGROUND: Surgical site infection (SSI) in spinal surgery contributes to significant morbidity and healthcare resource utilization. Few studies have directly compared the rate of minimally invasive surgery (MIS) SSI with open surgery. OBJECTIVE: To investigate whether MIS techniques had a lower SSI rate in degenerative lumbar procedures as compared with traditional open techniques. METHODS: A single-center, retrospective review of a prospectively collected database was queried from January 2013 to 2016 for adult patients who underwent lumbar decompression and/or instrumented fusion for which the surgical indication involved degenerative disease. The SSI rate was determined for all procedures as well as in the open and minimally invasive groups. Risk factors associated with SSI were also reviewed for each patient. RESULTS: A total of 1442 lumbar spinal procedures were performed during this time period. Of these, there were 961 MIS and 481 open (67% vs 33%, respectively). The overall SSI rate was 1.5% (21/1442). The surgical site infection rate for MIS was less than open techniques (0.5% vs 3.3%; P = .0003). For decompression only, the infection rate for MIS and open was 0.4% vs 3.9% ( P = .04), and for decompression with fusion it was 0.7% vs 2.6%, respectively ( P = .68). CONCLUSION: Our study demonstrates a significant 7-fold reduction in SSIs when comparing MIS with open surgery. This significance was also demonstrated with a 10-fold reduction for procedures involving decompression alone. Procedures that require fusion as well as decompression showed a trend towards a decreased infection rate that did not reach clinical significance.